Optimalisasi Penggunaan Alat Peraga Dalam Pembelajaran Ipa Di Min Ngestiharjo Wates - Sigit Prasetyo (LITERASI (Jurnal Ilmu Pendidikan), 2014)
The research aimed to discover the optimization of the use of the science kits in MIN Ngestiharjo Wates based on (1) the general condition of the school, including teachers’ and students’ condition, (2) the completeness of the science kits and it’s instructions, covering their conditions when received and their recent conditions, (3) the number and the use of the science kits in science study, (4) the frequency of the use of the science kits, (5) teachers’ knowledge of using the science kits, (6) teachers’ experiences in attending the training, and (7) teachers’ experiences and their opinions in using the science kits in science study. This research used the quantitative approach by the ki nd of survey research categories. Data were collected using questionnaires, observation, and interview to the officers. The instrument validity was assessed using the volume validities while the reliability was assessed using the triangulation method. Data were analyzed using the descriptive analysis technique. Findings show that the using of the science kits is not optimal based on, first, the general condition of the school covering the comparison between total students and science kits is not in adequate condition and the number of the teachers is already adequate, nevertheless, their overall qualification was inadequate. Second, the number of the science kits was in complete condition but the instructions covering the science kits were good when they’re received and partly, they’re damaged (25.0%). Third, the science kits are used in some of the science Study (66.7%) and the use of them in group practical activities was lack (66.7%) meanwhile they were precisely adequate for the demonstration (33.3%). Fourth, the average utilization frequency of science kits is 12 times maximum usage. Fifth, the respondents already understood the goal of using the science kits. Sixth, there were only small part of the respondents attended the upgrading activities. Lastly, the respondents experienced some obstacles in using the science kits covering the science kits packages are not adequate enough, the lack of science kits upgrading activities, and the needs for more times in using the science kits so that the respondents propose the problemalternative solutions such as increasing the teachers equaling program, upgrading the science kits, improving the KKG qualities, teachers’ sharing, and other materials of references or associated (already performed). Otherwise, it is necessary to conduct the technical guidance especially for science teachers, improving the science upgrading program, improving the KKG qualities, increment the number of science kits, and separated timing allocation (hasn’t been performed).